The Ontological Foundations of Indonesia’s National Education System in the Light of Pancasila - Hasanah, Siti Arina; Ruhiyat, Asep Muhamad Maulana; Sauri, Sofyan; Hadad, Ilham Amar Nur (Pancasila and Law Review, 2025)
Critically examines Indonesia’s national education paradigm by addressing the ontological tension between contemporary scientific rationality and the ethical–constitutional foundations of Pancasila. Drawing on a qualitative philosophical approach grounded in systematic hermeneutic analysis of primary normative texts, including the 1945 Constitution and Law Number 20 of 2003, the study reveals a structural inconsistency between technocratic, value-neutral models of education governance and the constitutional mandate to develop complete and dignified human beings. The findings demonstrate that this inconsistency constitutes not merely a pedagogical concern but a normative and constitutional problem within national education law. By proposing an integrative framework that aligns holistic scientific ontology with Pancasila ethics, this article contributes a conceptual foundation for reconstructing national education governance in accordance with Indonesia’s constitutional values.